Revisiting the relationship between global and specific levels of foreign language boredom and language engagement: A moderated mediation model of academic buoyancy and emotional engagement - Liu , Honggang; Elahi Shirvan, Majid; Taherian, Tahereh (Studies in Second Language Learning and Teaching, 2024)
The current research aimed to examine the relationships among three key aspects of the language learning process, namely, foreign language boredom (FLB), English language engagement (ELE), and academic buoyancy (AB), utilizing data collected from 2,992 Chinese language learners. In order to strengthen the accuracy and robustness of the results, we initially performed primary analyses to determine the most effective measurement solution for the three variables. As a result, we decided to use a bifactor exploratory structural equation modeling (ESEM) solution for FLB, a partial bifactor-ESEM solution for ELE, and a unidimensional confirmatory factor analysis solution for AB. The primary analysis demonstrated that the global factor of FLB strongly and negatively influenced the global levels of ELE. Both global and specific factors of FLB predicted different facets of specific ELE differently. The mediation-moderation analysis further confirmed the significance of the specific factors of emotional ELE as mediators and AB as a moderator in the relationships between global and specific levels of FLB and global and specific levels of ELE. The findings offer a basis for theoretical and pedagogical implications.